IMPRESSIVE BENEFITS OF EUCALYPTUS LEAVES (The Research of Medical Science Review, 2024)
With a specific focus on Eucalyptus camaldulensis, this study explores the chemical makeup and therapeutic uses of various Eucalyptus species. Numerous bioactive substances,including tannins, saponins, alkaloids, flavonoids, terpenoids, glycosides, anthraquinones,and steroids, have been found in diverse plant components by thorough phytochemical investigations.. Eucalyptus camaldulensis essential oil was extracted by steam distillation, and its constituents—p-cymene, 18-cineole, beta-phellandrene, spathulenol, and cryptone—were identified by gas chromatography and mass spectrometry analysis. These compounds are associated with a multitude of therapeutic properties, including antibacterial, antioxidant, and anti-inflammatory properties. The study highlights the plant's potential for use in pharmaceutical and industrial applications, as well as its widespread use in traditional medicine to treat a variety of ailments. Additionally, the study discusses how growth methods and environmental variables can vary the chemical makeup of plants, highlighting the necessity of consistent quality control in the eucalyptus essential oil production process. This study advocates for more research into the pharmacological mechanisms and potential therapeutic benefits of Eucalyptus species, consolidating current knowledge on their medicinal-usefulness.